A metal-free one-pot synthesis of benzo[c]chromen-6-ones from 3, 4-dichlorocoumarins and butadienes using tandem photo-thermal-photo reactions. Issue 41 (28th September 2016) - Zhang, Yan; Tian, Yan; Xiang, Pei; Huang, Ning; Wang, Jianyi; Xu, Jian-Hua; Zhang, Min
Abstract : A concise one-pot synthesis of benzo[ c ]chromen-6-ones from dichlorocoumarins and butadienes has been achieved, using a photo-initiated formal Diels–Alder reaction, with high overall yields. Abstract : An efficient, simple and versatile synthesis of biologically valuable benzo[ c ]chromen-6-ones is achieved using a tandem photo-thermal-photo reaction sequence starting from 3, 4-dichlorocoumarins and a 1, 3-butadiene. In this concise one-pot protocol, neither metal catalyst nor peroxide promoter is needed and the products can be purified through simple recrystallization in most cases. The synthesis consists of a reaction sequence of photo-induced [4 + 2] and [2 + 2] cycloadditions, silica gel promoted elimination of HCl and electrocyclic cyclobutene ring opening followed by a photo-induced 6π electrocyclization. The reactions proceed well with a range of dichlorocoumarins and some typical butadienes to provide the corresponding annulated products in 70–80% yield.